The XIV AESOP Congress in Brno, 19.-22. July 2000 - Schmeidler, Karel (Urban Planning Institute of the Republic of Slovenia, 2000)
The XIV European Congress of the Association of European Schools of Planning (AESOP)2 was ceremonially opened on Wed- nesday 19 July 2000 in the Ro- tunda of Pavilion A at Brno Exhi- bition Centre. The motto of this year«s congress was »Planning at a Turning Point«. The most im- portant event in AESOP«s pro- gramme is its annual congress, where a broad spectrum of work from individual schools is put for- ward. It also features presenta- tion of scientific research work and educational work, and dis- cussion of individual topics rela- ting to, for example, town and land planning, issues in the so- ciology of towns and cities, settle- ment geography, regional issues, the economy of towns and cities, and the legal issues involved in planning. The congress is usually accompanied by local excursions, business negotiations and mee- tings of interest groups. Congres- ses are held in member countries, and focus on particular issues depending on the specific condi- tions of the time. It is always or- ganised by a university with a good name in a specialist field. Each year those attending the congress take an interest in local town planning issues and draw up local studies.
Urbani Izziv 2000, 11 (2)